2023
DOI: 10.3390/diseases11010036
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis on the Effect of Sarcopenia in Patients with Knee Osteoarthritis before and after Total Knee Arthroplasty

Abstract: Introduction: Primary sarcopenia is an age-related disease that occurs mainly in older adults, while its possibility of appearance increases with age. Secondary sarcopenia is related to the presence of a disease. At times, studies have implied a connection between various diseases and the appearance of sarcopenia. Due to pain, patients with knee osteoarthritis limit their everyday activities, leading to a decrease in muscle mass and physical function. Purpose: This study aimed to investigate the impact of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…On the other hand, a systematic review and meta-analysis showed that the prevalence of sarcopenia was more than twice as high in patients with osteoarthritis of the knee compared with controls ( Pegreffi et al, 2023 ). However, there are also some studies do not agree with the aforementioned notion, and they consider the interconnection of the two to be highly controversial ( Jones et al, 2021 ; Mezian et al, 2021 ; Tzartza et al, 2023 ). In addition, for ethical and practical purposes, a causal association between the two diseases could not be proved by a randomized controlled trial (RCT).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a systematic review and meta-analysis showed that the prevalence of sarcopenia was more than twice as high in patients with osteoarthritis of the knee compared with controls ( Pegreffi et al, 2023 ). However, there are also some studies do not agree with the aforementioned notion, and they consider the interconnection of the two to be highly controversial ( Jones et al, 2021 ; Mezian et al, 2021 ; Tzartza et al, 2023 ). In addition, for ethical and practical purposes, a causal association between the two diseases could not be proved by a randomized controlled trial (RCT).…”
Section: Introductionmentioning
confidence: 99%